(untitled) (Research, Society and Development, 2020)
The way we produce and receive information has been changing rapidly with advances in the area of Information and Communication Technology. Among the advances we can highlight the Internet of Things, a concept that seeks to expand internet access for all objects that, once connected, can generate data and become active agents in the construction of information. Through this bibliographic review we seek to understand how the Internet of Things will affect the area of education by analyzing its opportunities and challenges in this field. Although this is a new technology, there are already several initiatives to apply this concept to teaching, in this work, in addition to presenting its general characteristics, we also try to indicate which ones have stood out positively and which tend to consolidate in the coming years.